From the Roads of Ruins to the Path of Prosperity - A Success Story of Rehdhar Watershed, District Jalaun, U.P. - Bhan, Suraj; Singh, R.A. (Journal of Soil and Water Conservation, 2022)
With a view to optimising the production of all available resources in the watershed area through improved soil and water management practices, water harvesting and sckntific crop management an Operational Research Project was undertaken on 748 ha land at village ’Rendhar’ in district Jalaun during 1983-84 to 1991-92. The project area zvas badly eroded and ravinous due to fivc nalas (drains) passing through the area bringing runoff from about 36 km area having their confluence at village Rendhar from where the Bhadya Nala emanates and cultivates to river Pahuj a tributary of river Yamuna. The initial productivity of crops was extremely poor registering 4.5, 5.6, 4.6 q/h for lower, Arhar and Bajra respectively and 10.0, 6.2, 6.5, 2.5 and 5.8 q/ha for wheat, gram, barley, mustard and lentil respectively. The area was treated by various soil and water conservation measures in- cluding contour building, submergence bunding, gully plugging, construction of check dams for water harvesting, farm ponds, including introduction of improved seeds, substitution of traditional crops and cropping systems by improved ones, fertilizer use, irrigation and alternate land use systems with emphasis on dryland horticulture and agro-forestry were followed through field demonstrations, block demonstrations, adoptive trials, farmers training and spot guidance. Through the eight years of the programme, the increased use of improved seed, fertilizer, irrigation and power have brought about 3 to 6 fold, increase in productivity of crops, 84% increase in cropping intensity and 6 to 8 fold increase in total agricultural production in the area. The oil seeds, pulses, vegetables and fodder crops have shown phenomenal increase both in area and production. The fertilizer use which was almost nil at the time of commencement of the programme has increased to the level of 54.34, 47.37 and 5.32 tones of NPK, respectively during 1991-92. Likewise the irrigated area has increased from 56.2 ha during 1983-84 to 690 ha during 1991-92. The ground water which is being recharged by water harvesting in check dams is being exploited for irrigation and drinking by way of 30 dug wells and 47 shallow tubewells operated with diesel pun’ipsets during 1991- 92 as against 10 and nil respectively during 1983-84. The programme has brought about an alround improvement in productivity and prosperity in the area apart from generation of tremendous employment potential and control of the rush of run-off water of the 5 drains which was threatening the existence of village Rendhar. The 42.18, 17.00, 93.00, 160.00 and 185.70 ha arca of the project has been saturated with forest/horticultural trees, agro- fivestilt conservation ftwestry and pasture, respectively upto 1991-92 to meet the requirrnient °Hurl, fodder, fruits, etc., as against 17.08 ha in 1983-84.